Economics and gender : selected bibliography - Marco, Flavia (ECLAC SantiagoCL, 2002)
Seeks to facilitate the exchange and dissemination of information on gender and economics. Contributes to the research and analysis of phenomena associated with recent processes of globalization and economic liberalization and with changes in the roles performed by women and men, and the development policies adopted.